2022
DOI: 10.18502/ijph.v51i12.11467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic-Anaerobic Exercise on Social Avoidance, Positive and Negative Affects, and Self-Consciousness of Obese Women

Abstract: Background: We aimed to investigate the effects of aerobic-anaerobic exercise on social avoidance, positive and negative emotions, and self-awareness in obese women as well as provide some basis for guiding them to increase their physical exercise and promote physical and mental health. Methods: Sixty obese women (body mass index≥23 kg/m2) who volunteered to participate in the experiment were selected in Tianjin, China in 2022, and divided into control group and observation group with 30 people in each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Kagawa et al [57] found that as the physical activity-pleasure index (PA-PI) increased, avoidance/rumination behaviors gradually decreased. Aerobic-anaerobic exercise can improve body composition and shape in obese women, enhance self-image and self-awareness, reduce social avoidance and distress, and achieve the goal of boosting self-esteem, confidence, and social skills [58]. Based on previous research, it can be inferred that there may be a negative correlation between physical activity and social avoidance.…”
Section: The Mediating Role Of Social Anxiety and Self-disclosurementioning
confidence: 99%
“…Kagawa et al [57] found that as the physical activity-pleasure index (PA-PI) increased, avoidance/rumination behaviors gradually decreased. Aerobic-anaerobic exercise can improve body composition and shape in obese women, enhance self-image and self-awareness, reduce social avoidance and distress, and achieve the goal of boosting self-esteem, confidence, and social skills [58]. Based on previous research, it can be inferred that there may be a negative correlation between physical activity and social avoidance.…”
Section: The Mediating Role Of Social Anxiety and Self-disclosurementioning
confidence: 99%